Correlation Among Rainfall, Humidity, and The El NiÃ±o-Southern Oscillation (ENSO) Phenomena in Bengkulu City During the Period from 1985-2020 - Agam Wardani; Arya J Akbar; Lina Handayani; Ashar Muda Lubis (Jurnal Penelitian Pendidikan IPA, 2023)
A correlation analysis is needed to see the relations among the three variables, rainfall with El NiÃ±o-Southern Oscillation (ENSO) and Humidity with ENSO. The instability of rainfall and the decrease in the humidity in Bengkulu City can be affected by La Nina and El Nino phenomena. This research aimed to analyze the correlations among rainfall, humidity, and ENSO with Pearson correlation analysis. The rainfall and humidity data were collected from BMKG, and the ENSO data were obtained from NOAA PSL for the 1985-2020 period. The results of the correlation analysis of rainfall and ENSO for the last 35 years generally show a moderately strong correlation. However, a strong correlation in the La Nina phase specifically occurred in 1988-1989, 1998-1999, 1999-2000, 2007-2008 and 2010-2011 with values of 58.6, 40.1, 61.4, 96, 4, and 89.2%. Meanwhile, the correlation >80% (very strong) during the El Nino phase occurred in 1987, 1991-1992, 1997, 2015. The correlation analysis results of humidity and ENSO show little correlation in the La Nina phase of >70% (1988-1989, 1998-1999, 2010-2011) and the El Nino phase of <70% (1997, 2015, 2016). The humidity correlations with ENSO do not influence the humidity change in Bengkulu City. The decrease in the humidity in Bengkulu City can be affected by other factors, such as land use change to housing due to population growth in Bengkulu City.